Clinico-genomic findings, molecular docking, and mutational spectrum in an understudied population with breast cancer patients from KP, Pakistan - Ahmad, Hilal; Ali, Asif; Khalil, Ali Talha; Ali, Roshan; Khan, Ishaq; Khan, Mah Muneer; Ahmed, Ibrar; Basharat, Zarrin; Alorini, Mohammed; Mehmood, Amna (Frontiers in Genetics, 2024)
Here we report the mutational profiles, pathogenicity and their association with different clinicopathological and sociogenetic factors in patients with Pashtun ethnicity for the first time. A total of 19 FFPE blocks of Invasive Ductal Carcinoma (IDC) from the BC tissue and 6 normal FFPE blocks were analyzed by Whole Exome Sequencing (WES). Various somatic and germline mutations were identified in cancer related genes i.e., ATM, CHEK2, PALB2 and XRCC2. Among a total of 14 were germline and four were somatic mutations. The ATM gene exhibited the maximum number of mutations (11/18) , followed by CHEK2 (3/18), PALB2 (3/18) and XRCC2 (1/18). Except one frame-shift deletion, all other 17 mutations were nonsynonymous single nucleotide variants (SNVs). SIFT prediction revealed 7/18 (38.8%) mutations as deleterious. PolyPhen-2 and Mutations Taster identified 5/18 (27.7%) as probably damaging and 10/18 (55.5%) as disease causing respectively. Mutations like PALB2 p.Q559R (6/19; 31.5%), XRCC2 p.R188H (5/19; 26.31%) and ATM p.D1853N (4/19; 21.05%) were recurrent mutations and proposed to have a biomarker potential. The protein network prediction was performed using GeneMANIA and STRING. ISPRED-SEQ indicated three interaction site mutations which were further used for the molecular dynamic simulation. An average increase in the radius of gyration was observed in all mutated proteins revealing their perturbed folding behavior. Obtained SNVs were further corelated with various parameters related to clinicopathological status of the tumors. Three mutation positions (ATM p. D1853N, CHEK2 p. M314I, and PALB2 p.T1029S) were found to be highly conserved. Finally, the wild and mutant type proteins were screened for two drugs: Elagolix (Drugbank ID: DB11979), and LTS0102038 (a triterpenoid, isolated from anticancer medicinal plant Fagonia indica). Comparatively higher number of interactions were noted for normal ATM with both compounds as compared to mutants.